2018
DOI: 10.5194/nhess-2018-158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flood depth estimation by means of high-resolution SAR images and LiDAR data

Abstract: Abstract. When floods hit inhabited areas, great losses are usually registered both in terms of impacts on people (i.e., fatalities and injuries) as well as economic impacts on urban areas, commercial and productive sites, infrastructures and agriculture. To properly assess these, several parameters are needed among which flood depth is one of the most important as it governs the models used to compute damages in economic terms. This paper presents a simple yet effective semi-automatic approach for deriving ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Flood depth is also important because it explains the level of possible damage, thereby helping to estimate the probable losses (Mojtahed et al, 2013; Scorzini & Frank, 2017). Hence, it has a strategic role in assisting emergency response through evaluating the accessibility of the area and crafting appropriate mediation plans (Cian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flood depth is also important because it explains the level of possible damage, thereby helping to estimate the probable losses (Mojtahed et al, 2013; Scorzini & Frank, 2017). Hence, it has a strategic role in assisting emergency response through evaluating the accessibility of the area and crafting appropriate mediation plans (Cian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Developing space‐based technology, which includes remote sensing coupled with GIS, has enriched the estimation of flood extents through satellite imagery. Several studies such as Cian et al (2018), Matheswaran et al (2019) and Nharo et al (2019) have furthered the science of flood inundation mapping through satellite images and surface elevation data. For example, Sanyal and Lu (2004) applied remote sensing data for FRM in Monsoon Asia and concluded that the data were more effective for flood extent delineation in developing countries.…”
Section: Flood Inundation Mappingmentioning
confidence: 99%
“…Precipitation events have as a result long-lasting cloud coverage periods and SAR sensors' ability to penetrate clouds both day and night make them more suitable for the task. Lidar technologies can give precise Digital Elevation Models that can be combined with SAR to estimate flood extend along with precise depth [47]. Sentinel-2 multispectral imagery and CNN's have been used in supervised classification producing good results but in limited spatial scale (national) and water segmentation for labeling was produced by visual interpretation with results relative to a human analyst and not in absolute ground truth [48] .…”
Section: B Remote Sensing and Flood Detectionmentioning
confidence: 99%
“…It aims at discriminating the two classes, namely wet pixels (for flooded areas) and dry pixels in SAR images by estimating their respective backscatter intensity distribution. Cian et al [24] proposed a two-step flood depth estimation using different RS datasets. Firstly, the flood extents were delineated on SAR images using Normalized Difference Flood Index [25], computed based on the SAR images taken before and and after a flood event.…”
Section: Remote Sensing Flood Extent Observation For Calibration And/...mentioning
confidence: 99%